Comparative study on optical and radiation shielding properties of Dy3+ doped boro-tellurite glass with varied BaO, Bi2O3, Nb2O5, and WO3 compositions - Yusof, N.N.; Asyiqa, A.Z.N. Farah; Iskandar, S.M.; Mohyedin, Muhammad Zamir; Hisam, R.; Azlan, M.N.; Zaid, M.H.M.; Zuber, S.H.; Hadi, M.F.R. Abdul; Seitkhan, Azat (Elsevier, 2025)
Raise demand on transparent and lead-free radiation shielding in medical imaging has led new composition design. This study examines optical and radiation shield properties of Dy3+ ion-doped boro-tellurite glasses with different metal oxide contents which are BaO, Bi2O3, Nb2O5, and WO3 at 5 mol% concentration. The glasses containing Bi2O3 and BaO shows the strongest absorbance intensities at 1289 nm (6H15/2 → 6F11/2) and 573 nm (4F9/2 → 6H13/2), respectively. Phy-X simulations calculate the key parameters including linear attenuation coefficient (LAC), mass attenuation coefficient (MAC), half-value layer (HVL), and mean free path (MFP). Glass doped with Bi2O3 demonstrated superior shielding performance with the highest MAC (257.1256–0.03652 cm2/g), LAC (1210.4869–0.1719 cm−1), HVL (0.0006–4.0318 cm), and the lowest MFP (0.001–5.817 cm) across the 0.008–15.000 MeV range. A high MAC and LAC indicate superior radiation shielding efficiency by maximizing photon absorption, minimizing material thickness, and ensuring effective protection across a broad energy range. These results highlight the potential of Bi2O3-containing Dy3+ doped boro-tellurite glasses as effective transparent radiation shielding materials, suitable for advanced medical imaging and nuclear medicine applications.